2017
DOI: 10.1038/aps.2016.180
|View full text |Cite
|
Sign up to set email alerts
|

Sarsasapogenin-AA13 inhibits LPS-induced inflammatory responses in macrophage cells in vitro and relieves dimethylbenzene-induced ear edema in mice

Abstract: Sarsasapogenin-AA13 (AA13) is a novel synthetic derivative of sarsasapogenin extracted from the Chinese herb Rhizoma Anemarrhenae. In this study we investigated the effects of AA13 on lipopolysaccharide (LPS)-induced production of inflammatory factors in macrophage cells and the anti-inflammatory activity of AA13 in an inflammatory model of dimethylbenzene-induced ear edema. Macrophage cells (RAW264.7 cells and mouse peritoneal macrophages) were exposed to LPS (1 μg/mL); pretreatment with AA13 (5-20 μmol/L) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(47 reference statements)
1
18
0
Order By: Relevance
“…17 More studies have also shown that its derivatives are effective in anti-inflammatory, neuroprotective, and memory impairment related to aging. 21,22 However, the role of sarsasapogenin in osteoclast formation and bone resorption has not been reported. Thus, the effects of sarsasapogenin on these areas remain to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…17 More studies have also shown that its derivatives are effective in anti-inflammatory, neuroprotective, and memory impairment related to aging. 21,22 However, the role of sarsasapogenin in osteoclast formation and bone resorption has not been reported. Thus, the effects of sarsasapogenin on these areas remain to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we synthesised several carbamate derivatives exhibiting neuroprotective and NO production inhibitory properties (Pan, Van Khang, Dong, Wang, & Ma, ). Among all the derivatives, AA13 has emerged as one of the most useful compounds to inhibit inflammatory reactions and ameliorate Aβ‐induced cognitive deficits (Dong et al, ; Huang et al, ). AA13 also shows neuroprotective effect on Alzheimers disease (AD) model by promoting Aβ clearance and shifting pro‐inflammatory M1 to anti‐inflammatory M2 phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…This worsened outcome at the experimental level has been attributed to an entity known as reperfusion injury (R/I) [3]. It results in activation of inflammatory processes that cause secondary tissue injury [4]. Anti-inflammatory Targets may be a promising therapeutic strategy to attenuate the progression of ischemic brain injury.…”
Section: Introductionmentioning
confidence: 99%